A Multicenter Randomized Bioequivalence Study of a Novel Ready-to-Use Temozolomide Oral Suspension vs. Temozolomide Capsules - François Ducray; Carole Ramirez; Marie Robert; Maxime Fontanilles; Charlotte Bronnimann; Olivier Chinot; Florian Estrade; Xavier Durando; Stéphanie Cartalat; Jeremy Bastid; Hugues Bienayme; Caroline Lemarchand (Pharmaceutics, 2023)
Background: Temozolomide (TMZ) oral suspension (Ped-TMZ, KIZFIZO®) is being developed for the treatment of relapsed or refractory neuroblastoma, a rare cancer affecting infants and young children. The study assessed the safety and the bioequivalence of this novel pediatric formulation with existing TMZ oral capsules. Methods: In vitro dissolution profiles and the bioequivalence were evaluated following the European Medicines Agency “Guidelines on the investigation of Bioequivalence”. The phase I, multicenter, randomized, open-label, crossover, single-dose bioequivalence study enrolled 36 adult patients with glioblastoma multiforme or lower-grade glioma. Each patient received 200 mg/m2 Ped-TMZ suspension and TMZ capsules (Temodal®) on 2 consecutive days, with the order being randomly assigned. Fourteen blood samples were collected up to 10 h post-dosing. Bioequivalence was assessed by comparing the 90% confidence interval for the ratio of the geometric means of maximum TMZ plasma concentration (Cmax) and the area under the curve (AUCt). Other endpoints included further pharmacokinetic parameters and safety. Results: Both formulations exhibited a fast in vitro dissolution profile with more than 85% of TMZ dissolved within 15 min. For the bioequivalence study, thirty patients completed the trial as per the protocol. The ratio of Ped-TMZ/TMZ capsule geometric means (90% CI) for AUCt and Cmax were 97.18% (95.05–99.35%) and 107.62% (98.07–118.09%), respectively, i.e., within the 80–125% bioequivalence limits. No buccal toxicity was associated with Ped-TMZ liquid formulation. Conclusions: This study showed that Ped-TMZ oral suspension and TMZ oral capsule treatment are immediate release and bioequivalent medicines. There were also no unexpected safety signals or local toxicity (funded by ORPHELIA Pharma; ClinicalTrials.gov number, NCT04467346).